Perceptions and prevention practices on malaria among the indigenous Orang Asli community in Kelantan, Peninsular Malaysia - Munajat, Mohd Bakhtiar; Rahim, Mohd Amirul Fitri A.; Wahid, Wathiqah; Rakna, Mohd Ikhwan Mukmin Seri; Divis, Paul Cliff Simon; Chuangchaiya, Sriwipa; Lubis, Inke Nadia D.; Osman, Emelia; Kasri, Muhd Rafiq Mohd; Idris, Zulkarnain Md (BioMed Central Ltd, 2021)
Background Malaysia is on track towards malaria elimination. However, several cases of malaria still occur in the country. Contributing factors and communal aspects have noteworthy effects on any malaria elimination activities. Thus, assessing the community’s knowledge, attitudes and practices (KAP) towards malaria is essential. This study was performed to evaluate KAP regarding malaria among the indigenous people (i.e. Orang Asli) in Peninsular Malaysia.